The Impact of Lifestyle-related Factors on Survival After a Prostate Cancer Diagnosis - Darcey, Ellie; Pereira, Gavin; Salter, A.; Fritschi, Lin; Leavy, Justine; Ambrosini, G.L.; Boyle, Terry (ELSEVIER SCIENCE BV, 2019)
Research indicates that lifestyle-related factors such as obesity, physical activity, and smoking influence breast and colorectal cancer survival, but less is known about the association between lifestyle-related factors and survival in males with prostate cancer (PC). Recent reviews have investigated the impact of obesity on PC survival; however the small number of studies and significant heterogeneity in results make it difficult to draw firm conclusions [1]. Few studies have investigated the association between physical activity and PC survival [2]. More is known about tobacco smoking: a 2018 meta-analysis concluded that tobacco smoking at diagnosis is associated with poorer all-cause mortality (ACM) and PC-specific mortality (PSM) [3].